Avoiding Corrosion Problems in Florida - Virginia Peart (EDIS)
Corrosion is a naturally occurring deterioration of a metal caused by reaction with its environment and especially with oxygen. The result is the production of brown rust on iron or steel, white spots or surface discoloration on aluminum and blue or green layers on copper. Moisture, oxygen and a salt (e.g. sodium chloride) all contribute to the corrosion process. In a humid climate, especially in coastal areas where moisture is saline or salty, corrosion can occur readily. This is document FCS3141, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: January 2003. First published: February 1989. Reviewed: January 2003.